Detection of cefotaxime-resistant CTX-M-3 in clinical isolates of Serratia marcescens - Tsou, Mei-Fen; Yu, Wen-Liang; Hung, Siu Wan; Chi, Chizh-Ju; Chieh-Ju; Chen, Ssu Ching; Wu, Lii-Tzu (Folia microbiologica, 2004)
Strains of Serratia marcescens (isolated in a hospital during April and August 2000) resistant to ampicillin, chloramphenicol, trimethoprim-sulfamethoxazole, streptomycin, tetracycline, and gentamicin were characterized. Out of a total of 34 clinical isolates 6 (17.6 %) exhibited the extended spectrum beta-lactamases (ESBL) resistance; they were also resistant to cefotaxime (minimum inhibitory concentration, MIC > or = 128 microg/mL) but susceptible to imipenem (MIC < or = 0.5 microg/mL). This multidrug resistance was shown to be transferred by a conjugative plasmid. Transconjugants revealed similar MIC profiles when compared to the parental strains. Isoelectric focusing revealed one major transferable beta-lactamase (pI 8.4) which was further identified as CTX-M-3 by PCR and gene sequencing. The presence of strains with this type of ESBL showed the evolution of bla genes and their dissemination among at least three species of the family Enterobacteriaceae isolated within a single hospital. The predominance of CTX-M type enzymes found in this area of Taiwan appeared to be similar to that described in Poland.
Keywords: Conjugation, Genetic; Drug Resistance, Bacterial; beta-Lactamases; Microbial Sensitivity Tests; Serratia marcescens; Cefotaxime; konjugace genetická; cefotaxim; lidé; beta-laktamasy; Humans; bakteriální léková rezistence; mikrobiální testy citlivosti